Bacteriophage Treatment Induces Phenotype Switching and Alters Antibiotic Resistance of ESBL Escherichia coli - Árpád Rózsa; László Orosz; Nikoletta Szemerédi; Gabriella Spengler; Gábor Kecskeméti; Otília Vágó; Károly Péter Sárvári; Diana Szabó; Zoltán Szabó; Katalin Burián; Dezső Péter Virok (Antibiotics)
Background/Objectives: Bacteriophage therapy represents a promising strategy to combat multidrug-resistant pathogens, such as Escherichia coli. In this study, we explored the effects of a bacteriophage infection on an Extended Spectrum Beta-Lactamase (ESBL) positive E. coli isolate. Methods: We used next generation sequencing, proteomics and phenotypic screens to investigate the effect of bacteriophage infections on E. coli metabolism and resistance phenotypes. Results: The bacteriophage infection led to notable alterations in colony morphology, indicating profound changes in bacterial metabolism. Proteomic analysis revealed significant shifts in protein expression, with 65 proteins upregulated and 246 downregulated post-infection. The downregulated proteins were involved in various metabolic pathways, including nucleic acid, protein and lipid metabolism, and iron acquisition. Bacteriophage treatment also led to increased bacterial membrane permeability. Altogether, these alterations in bacterial metabolism and membrane permeability may lead to a general reduction in antibiotic resistance. Indeed, the bacteriophage-infected E. coli exhibited increased sensitivity to various classes of antibiotics, including beta-lactams, fluoroquinolones, trimethoprim-sulfamethoxazole, and aminoglycosides. Conclusions: Our findings highlight the potential of bacteriophage therapy as an adjunct to existing antibiotics, enhancing their efficacy against resistant strains.